Income inequality and elections’ funding : evidence from Brazil and Japan - Roviello, Felipe Yudi Yamashita (2021)
Dissertação (mestrado) — Universidade de Brasília, Faculdade de Economia, Administração, Contabilidade e Gestão de Políticas Públicas, Departamento de Economia, 2021.